2022
DOI: 10.1186/s12944-022-01715-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific changes in triglyceride profiles in liver cirrhosis and hepatitis C virus infection

Abstract: Background Hepatitis C virus (HCV) infection is associated with serum lipid abnormalities, which partly normalize following direct-acting antiviral (DAA) therapy. Here, associations of serum triglycerides (TGs) with viral genotype and markers of liver disease severity were evaluated in patients with chronic HCV.  Methods The study included the serum of 177 patients with chronic HCV. TGs were quantified by flow injection analysis Fourier transform m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
1
0
0
Order By: Relevance
“…A recent report of triglyceride profiles in sera from 177 HCV patients found that serum triglycerides were lower in male patients with cirrhosis than in male patients without cirrhosis after DAA therapy. Overall, triglyceride levels did not change in either sex after DAA therapy [ 32 ]: a finding consistent with our observations reported here. This same group investigated eight serum ceramide concentrations in 178 patients with chronic HCV infection and noted that most ceramides are carried on LDL, which rises after effective DAA therapy.…”
Section: Discussionsupporting
confidence: 91%
“…A recent report of triglyceride profiles in sera from 177 HCV patients found that serum triglycerides were lower in male patients with cirrhosis than in male patients without cirrhosis after DAA therapy. Overall, triglyceride levels did not change in either sex after DAA therapy [ 32 ]: a finding consistent with our observations reported here. This same group investigated eight serum ceramide concentrations in 178 patients with chronic HCV infection and noted that most ceramides are carried on LDL, which rises after effective DAA therapy.…”
Section: Discussionsupporting
confidence: 91%